Utilization of Digital Learning Media to Increase Students’ Learning Interest: A Qualitative Study in Grade III of Islamic Elementary School - Hanifah, Nur; Nuzilatus Shoimah, Retno (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study aims to analyze the role of digital learning media in increasing students' learning interest at the elementary school level, particularly in Islamic Elementary Schools (MI). The background of this study is based on the need to present a more interactive, engaging learning process that is in accordance with the developmental characteristics and life context of students. Theoretically, this study refers to the Multimedia Learning Theory proposed by Richard E. Mayer which emphasizes the importance of integrating visual and audio elements in improving learning comprehension, as well as the ARCS motivation model by John M. Keller which includes aspects of attention, relevance, confidence, and satisfaction in increasing students' learning motivation. This study uses a descriptive qualitative approach with data collection techniques through observations of the learning process in the classroom, interviews with teachers and students, and visual documentation as supporting data. Data analysis was conducted to describe in depth the impact of the use of digital learning media on students' learning interest and participation. The results of the study indicate that the use of digital learning media has several positive impacts, including increased student attention during the learning process, presentation of materials that are more contextual and easy to understand, increased student courage to actively participate in learning activities, and the growth of a sense of enjoyment and motivation to learn. Digital media such as animated videos, interactive quizzes, and educational games have been proven to create more engaging and participatory learning experiences. However, the implementation of digital learning media still faces several technical challenges, such as limited supporting devices and teacher competency in utilizing learning technology. Therefore, improving teacher competency through ongoing training and providing adequate facilities and infrastructure is necessary to ensure optimal and sustainable use of digital learning media to increase student learning interest.